Urgensi Kegiatan Wirausaha MBKM Untuk Mewujudkan Profil Lulusan PAI UIN Sunan Kalijaga - Rahmah, Rafiqah Dwi; Sukiman, Sukiman (Research and Development Journal of Education, 2024)
Education is the main ammunition in forming a superior generation that has character, competitiveness and collaboration. Everyone certainly hopes that after they have completed 12 years of compulsory education and are in college they can get a job in the expert field they have studied, but the reality that we can see in society is that this is an asymmetric ratio. literature research which is described critically by using data collection techniques in the form of documentation, namely reading and noting. In this study using primary data sources and secondary data as a support and complement of primary data. Writing this article aims to find out the MBKM curriculum development model in entrepreneurial activities and urgency to realize the profile of PAI graduates at UIN Sunan Kalijaga. The results of this research state that the curriculum development model must still be adapted to the policies of each tertiary institution and in the current era it is important to have abilities outside the expert field that is being occupied by each student, one of which is edupreneur skills. It is hoped that this paper can assist in preparing the implementation of the MBKM policy at each tertiary institution. In line with that, one of the profiles of PAI graduates at UIN Sunan Kalijaga is to become edupreneurs in the field of creative and innovative IT-based Islamic education. Therefore, tertiary institutions are required to be responsive in designing and implementing educational processes that are creative, innovative, and progressive and oriented towards meeting comprehensive and relevant learning outcomes.